GmWRKY54 improves drought tolerance through activating genes in abscisic acid and Ca2+ signaling pathways in transgenic soybean. (2nd August 2019) - Wei, Wei; Liang, Da‐Wei; Bian, Xiao‐Hua; Shen, Ming; Xiao, Jian‐Hui; Zhang, Wan‐Ke; Ma, Biao; Lin, Qing; Lv, Jian; Chen, Xi; Chen, Shou‐Yi; Zhang, Jin‐Song
Summary: WRKY transcription factors play important roles in response to various abiotic stresses. Previous study have proved that soybean GmWRKY54 can improve stress tolerance in transgenic Arabidopsis. Here, we generated soybean transgenic plants and further investigated roles and biological mechanisms of GmWRKY54 in response to drought stress. We demonstrated that expression of GmWRKY54, driven by either a constitutive promoter (p Cm ) or a drought‐induced promoter ( RD29a ), confers drought tolerance. GmWRKY54 is a transcriptional activator and affects a large number of stress‐related genes as revealed by RNA sequencing. Gene ontology (GO) enrichment and co‐expression network analysis, together with measurement of physiological parameters, supported the idea that GmWRKY54 enhances stomatal closure to reduce water loss, and therefore confers drought tolerance in soybean. GmWRKY54 directly binds to the promoter regions of genes including PYL8, SRK2A, CIPK11 and CPK3 and activates them. Therefore GmWRKY54 achieves its function through abscisic acid (ABA) and Ca 2+ signaling pathways. It is valuable that GmWRKY54 activates an ABA receptor and an SnRK2 kinase in the upstream position, unlike other WRKY proteins that regulate downstream genes in the ABA pathway. Our study revealed the role of GmWRKY54 in drought tolerance and further manipulation of this gene should improve growth and production in soybean and other legumes/crops under unfavorable conditions. Significance Statement: This paper reveals that GmWRKY54 is a transcription factor that effectively modulates drought signaling, GmWRKY54 affects expression of large numbers of downstream genes that possess positive roles in drought tolerance. Using a precise analysis strategy of gene enrichment and co‐expression, it was discovered that GmWRKY54 confers drought tolerance through participating in the ABA and Ca 2+ signaling pathways.